International synthetic biology policy developments and implications for global biodiversity goals - Keiper, Felicity; Atanassova, Ana (Frontiers in Synthetic Biology, 2025)
In December 2022, the governments of 196 countries adopted the Kunming-Montreal Global Biodiversity Framework (KMGBF), a strategic plan to support and advance implementation of the objectives of the Convention on Biological Diversity (CBD) and its subsidiary agreements, including the Cartagena Protocol on Biosafety (Protocol). The KMGBF includes a “biosafety” target (Target 17), that reflects the CBD obligations for Parties to implement biosafety measures, and measures for handling biotechnology and distributing its benefits. The unprecedented inclusion of a biosafety target in the KMGBF, with explicit recognition of benefits and its placement amongst other targets for “tools and solutions for implementation and mainstreaming”, has ignited hope for renewed recognition of the potential for biotechnology to contribute to global environmental goals. This would mark a shift in this international forum that began with these intentions, but subsequently changed focus towards the potential adverse impacts of biotechnology and restrictive application of precaution. Simultaneously, a decade-long program of work on “synthetic biology” has been examining the implications of new developments in biotechnologies for the objectives of the CBD, with an emphasis on the scope and adequacy of existing biosafety measures, and more recently, “horizon scanning” for new technological developments. This review provides an overview of the status of biotechnology/synthetic biology policy developments under the CBD, focusing on the period from the drafting of the KMGBF in 2018 to current programs of work resulting from decisions made at the 2024 United Nations Biodiversity Conference. These are expected to have implications for biotechnology/synthetic biology capacity development and adoption, and implementation of the KMGBF. Relevant parallel policy developments under other international fora, including the International Union for the Conservation of Nature and Natural Resources (IUCN) and the Organisation for Economic Cooperation and Development (OECD), are also examined.